2015
DOI: 10.13044/j.sdewes.2015.03.0028
|View full text |Cite
|
Sign up to set email alerts
|

Towards New Renewable Energy Policies in Urban Areas: the Re-Definition of Optimum Inclination of Photovoltaic Panels

Abstract: The optimum inclination and orientation of fixed Photovoltaic (PV) panels has long been defined in terms of maximizing the annual electricity yield per capacity installed according to the hemisphere and latitude where the PV system is located. Such optimum setup would thus also maximize the output per system cost, but it would not maximize the output per unit of available area, and it would not necessarily optimize the contribution of photovoltaic electricity vis-à-vis overall electricity demand patterns. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Optimizing the tilt angle, panel facing, and distance between PV panel rows are suggested by Jouri, and Henrik, [7], for Lund and Miami cities, using a simulation program, they concluded that the maximum annual output can be achieved by choosing 0 ‫﮿‬ inclination without spaces between rows. Similar aspects studied by Weissenbacher, [8], and Castellano, et al, [9] In Baghdad city, where large number of sunny days during year, calculation of solar energy from collector panel array is very important to obtain the optimum array output. The aims of present work are:…”
Section: Introductionmentioning
confidence: 71%
“…Optimizing the tilt angle, panel facing, and distance between PV panel rows are suggested by Jouri, and Henrik, [7], for Lund and Miami cities, using a simulation program, they concluded that the maximum annual output can be achieved by choosing 0 ‫﮿‬ inclination without spaces between rows. Similar aspects studied by Weissenbacher, [8], and Castellano, et al, [9] In Baghdad city, where large number of sunny days during year, calculation of solar energy from collector panel array is very important to obtain the optimum array output. The aims of present work are:…”
Section: Introductionmentioning
confidence: 71%
“…However, some buildings can also shade their own envelope. If the building envelope shades the PV module, the shading must not exceed 10% of the total area of the PV module at any time between 10 a.m. and 2 p.m., when solar radiation is highest [66]. Such a repetitive modeling process from architectural design results in lost time, additional work, and possibly some loss of information (i.e., geometric and component inconsistencies due to incomplete understanding of the model).…”
Section: Discussionmentioning
confidence: 99%
“…Raptis et al [52] found an optimum tilt angle of 30° S in Athens. Lastly, the work by Weissenbacher [53] must be mentioned here as it gave a new definition for the optimal tilt angle of solar flat-plate convectors for energy policy makers.…”
Section: Introductionmentioning
confidence: 99%